Reinstating Fertility with Ayurveda: A Clinical Case Report on Shukra Kshaya (Low Sperm Count) (International Journal of Ayurveda and Pharma Research, 2025)
Male infertility is a significant reproductive health issue globally, with oligospermia- characterized by a low sperm count- being a leading cause. In Ayurveda, this condition is referred to as Shukra Kshaya, often resulting from Shukravaha Srotas Dushti (vitiation of the reproductive channels). Objective: To evaluate the effectiveness of Ayurvedic interventions in managing male infertility caused by Shukra Kshaya (Oligospermia). Method: A 36 years old male patient presenting with clinical signs of oligospermia underwent a treatment protocol based on Ayurvedic principles. The management included Aamapachana to eliminate metabolic toxins, followed by Vrushya and Rasayana therapy using herbal formulations Like Yashtimadhu, Ashwagandha, Bala Beeja, Shatavari, Musli, Gokshura, Chopchini and Phala Ghrita. Lifestyle and dietary modifications were also advised. Result: Post-treatment evaluation showed significant improvement in sperm count and motility. The patient reported enhanced sexual health and overall vitality. No adverse reactions were observed during the treatment course. Conclusion: Ayurvedic interventions, when appropriately selected and administered, can offer an effective, holistic, and non-invasive approach to managing male infertility associated with Shukra Kshaya (oligospermia). Further clinical trials are recommended to substantiate these findings and support their broader application.